2014
DOI: 10.2166/wst.2014.033
|View full text |Cite
|
Sign up to set email alerts
|

Study of the recovery of phosphorus from struvite precipitation in supernatant line from anaerobic digesters of sludge

Abstract: The goal of this work was to study the effective recovery of phosphorus from the supernatant of anaerobic digestion of sewage sludge by precipitation as struvite. The formation of struvite is envisioned as a promising process for nutrient removal and subsequent recovery, thus providing a strong incentive for its implementation, since the sewage is a renewable source of phosphorus. Struvite precipitation was obtained by controlled addition of Mg(OH)2 or MgCl2. We evaluated the removal of ammonia and phosphate u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…1.0 8.3 ± 0.9 10.4 ± 0.6 46.2 ± 2.1 13.1 ± 0.9 362 2.0 14.7 ± 1.2 22.9 ± 0.9 57.1 ± 1.1 18.6 ± 0.9 498 3.0 9.9 ± 1.1 11.6 ± 0.5 35.2 ± 1.7 8.6 ± 0.7 257 4.0 8.8 ± 1.1 12.5 ± 0.9 34 ± 0.4 9.8 ± 0.8 288 5.0 5.8 ± 0.3 8.2 ± 0.9 28.8 ± 1.7 9.8 ± 0.7 256 removal of phosphate, which was comparable to the reactor STR and Electrolyzer from previous studies (Aguado et al, 2019;Brown et al, 2018;Taddeo & Lepistö, 2015;Wang, Fu et al, 2019). In terms of nitrogen removal, the recent study achieved 56.0% which was higher than the STR reactor from the previous study (Xavier et al, 2014). A previous study reported that the struvite precipitation rate (in terms of phosphate removal rate) from the electrolyzer was about 70.46 mg L −1 h −1 to 396.65 mg L −1 h −1 .…”
Section: Effect Of Initial Ph On Nutrients Removal and Struvite Preci...supporting
confidence: 68%
See 1 more Smart Citation
“…1.0 8.3 ± 0.9 10.4 ± 0.6 46.2 ± 2.1 13.1 ± 0.9 362 2.0 14.7 ± 1.2 22.9 ± 0.9 57.1 ± 1.1 18.6 ± 0.9 498 3.0 9.9 ± 1.1 11.6 ± 0.5 35.2 ± 1.7 8.6 ± 0.7 257 4.0 8.8 ± 1.1 12.5 ± 0.9 34 ± 0.4 9.8 ± 0.8 288 5.0 5.8 ± 0.3 8.2 ± 0.9 28.8 ± 1.7 9.8 ± 0.7 256 removal of phosphate, which was comparable to the reactor STR and Electrolyzer from previous studies (Aguado et al, 2019;Brown et al, 2018;Taddeo & Lepistö, 2015;Wang, Fu et al, 2019). In terms of nitrogen removal, the recent study achieved 56.0% which was higher than the STR reactor from the previous study (Xavier et al, 2014). A previous study reported that the struvite precipitation rate (in terms of phosphate removal rate) from the electrolyzer was about 70.46 mg L −1 h −1 to 396.65 mg L −1 h −1 .…”
Section: Effect Of Initial Ph On Nutrients Removal and Struvite Preci...supporting
confidence: 68%
“…The recent study achieved 88.4% removal of phosphate, which was comparable to the reactor STR and Electrolyzer from previous studies (Aguado et al, 2019; Brown et al, 2018; Taddeo & Lepistö, 2015; Wang, Fu et al, 2019). In terms of nitrogen removal, the recent study achieved 56.0% which was higher than the STR reactor from the previous study (Xavier et al, 2014). A previous study reported that the struvite precipitation rate (in terms of phosphate removal rate) from the electrolyzer was about 70.46 mg L −1 h −1 to 396.65 mg L −1 h −1 .…”
Section: Resultscontrasting
confidence: 53%
“…Struvite precipitation offers a cost‐effective, relatively simple and functional method for phosphorus recovery from wastewater. This process serves several purposes: (i) it enables phosphorus recycling; (ii) it yields a product almost free of most organic micropollutants and traces of heavy metals, with high marketable value for agricultural use as slow release fertilizer; and (iii) it facilitates the pre‐treatment of urine, which makes urine a more suitable feed stream for bioelectrochemical systems (BESs), as explained later. The marketable value of struvite has also become important compared to that of phosphate ore, due to its high quality in terms of purity and low heavy metals content .…”
Section: Introductionmentioning
confidence: 99%
“…Struvite has the potential to be an effective slow‐release fertilizer (Talboys et al, 2016; Xavier et al, 2014). It has almost the same plant uptake efficiency as commercial fertilizers with a relative fertilizer efficiency (RFE) of almost 100% (Egle et al, 2016) and low solubility (solubility product pK so range of 9.4–13.26 based on Ohlinger et al, 1998; Doyle & Parsons, 2002).…”
Section: Resultsmentioning
confidence: 99%